Attack Trees with Sequential Conjunction - Jhawar, Ravi; Kordy, Barbara; Mauw, Sjouke; Radomirović, Saša; Trujillo-Rasua, Rolando (ICT Systems Security and Privacy Protection, 2015)
We provide the first formal foundation of SAND attack trees which are a popular extension of the well-known attack trees. The SAND attack tree formalism increases the expressivity of attack trees by introducing the sequential conjunctive operator $${\mathtt {SAND}}$$ . This operator enables the modeling of ordered events. We give a semantics to SAND attack trees by interpreting them as sets of series-parallel graphs and propose a complete axiomatization of this semantics. We define normal forms for SAND attack trees and a term rewriting system which allows identification of semantically equivalent trees. Finally, we formalize how to quantitatively analyze SAND attack trees using attributes.